การบริหารจัดการเพื่อให้บริการด้านการจัดเก็บขยะของกรุงเทพมหานครตามแนวคิดการบริหารจัดการที่ยั่งยืน ADMINISTRATION OF GARBAGE COLLECTION SERVICES OF THE BANGKOK METROPOLITAN ADMISTRATION ACCORDING TO THE SUSTAINABLE ADMINISTRATION CONCEPT - แจ่มวุฒิปรีชา, สีฟ้า (วารสารศรีนครินทรวิโรฒวิจัยและพัฒนา สาขามนุษยศาสตร์และสังคมศาสตร์, 2017)
บทคัดย่อ การศึกษาครั้งนี้มีวัตถุประสงค์เพื่อศึกษาการบริหารจัดการเพื่อให้บริการด้านการจัดเก็บขยะและพัฒนาแนวทางการบริหารจัดการที่ยั่งยื่น รวมถึงเสนอแนะยุทธศาสตร์การบริหารจัดการเพื่อให้บริการจัดเก็บขยะของกรุงเทพมหานครด้วยแนวคิดการบริหารจัดการที่ยั่งยืน ระเบียบวิธีวิจัย ใช้รูปแบบการวิจัยแบบผสมผสานโดยเน้นการวิจัยเชิงปริมาณและการวิจัยเชิงคุณภาพ เครื่องมือในการวิจัยนี้ใช้แบบสอบถามที่มีการค่าความเที่ยงตรงเท่ากับ 0.91 และค่าความเชื่อถือได้ที่ระดับ 0.83 ประชากร คือ ประชาชนทั้งหมดในเขตพื้นที่สำนักงานเขตในกรุงเทพมหานคร 4 เขต ได้แก่ เขตบางกอกน้อย เขตสวนหลวง เขตวังทองหลาง และเขตหลักสี่ 456,965 คน ส่วนกลุ่มตัวอย่างได้มาจากการคำนวณหาขนาดของกลุ่มตัวอย่างโดยใช้สูตรของ ทาโร่ ยามาเน่ จำนวน 1,112 คน วิธีวิเคราะห์ใช้รูปแบบการวิเคราะห์เชิงพรรณนา และสถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าเฉลี่ย ค่าเบี่ยงเบนมาตรฐาน การทดสอบค่าที ค่าการถดถอยพหุคูณ และการหาค่าสัมประสิทธิ์สหสัมพันธ์ของเพียร์สัน และการสัมภาษณ์แนวลึกเจากผู้เชี่ยวชาญ จำนวน 9 คน ผลการศึกษาพบว่า (1) ปัญหาเกี่ยวกับการบริหารจัดการที่สำคัญคือ ขาดการประชาสัมพันธ์หรือชี้แจงประชาชนในเรื่องการคัดแยกขยะโดยใช้เทคโนโลยี จึงควรประชาสัมพันธ์หรือให้ความรู้ประชาชนในเรื่องการคัดแยกขยะโดยใช้เทคโนโลยีที่เป็นเครือข่ายของกรุงเทพมหานครให้มากเพียงพอ เช่น สถานีวิทยุ โทรทัศน์ และกลุ่มในชุมชน รวมทั้งใช้เครือข่ายทางสังคม นอกจากนี้กรุงเทพมหานครควรกำหนดยุทธศาสตร์การบริหารจัดการเพื่อให้บริการด้านการจัดเก็บขยะ โดยเรียงตามลำดับความสำคัญจากมากไปน้อย ดังนี้ (1) ด้านการสร้างความรู้ความเข้าใจ (2) ด้านการจัดตั้งกลุ่มและแกนนำในชุมชน (3) ด้านการมุ่งพัฒนาประสิทธิภาพหน่วยงาน และบุคลากรต้นแบบ (4) ด้านการให้ความรู้ความเข้าใจ และการสร้างจิตสำนึกที่ดี และ (5) ด้านการใช้เทคโนโลยีที่เหมาะสม คำสำคัญ: การบริหารจัดการ การจัดเก็บขยะ กรุงเทพมหานคร แนวคิดการบริหารจัดการที่ยั่งยืน Abstract This research aims to study the administrative problem of garbage collection services of the Bangkok Metropolitan Administration (BMA) and the development guidelines of garbage collection services of the BMA according to the Sustainable Administration Concept. The questionnaires were used in this research which was passed pre-test of validity check at level of 0.91 and reliability check at level of 0.83. Population was all 456,965 residents in 4 the BMA’s District Offices as well as Bangkoknoi, Suanlaung, Wantthonglang, and Laksi. 1,112 samples of the residents were calculated by using Taro Yamane’s formula for sample size. Data analysis was represented in the descriptive analysis approach. Statistics applied were mean, standard deviation, multiple regression, and Pearson’s Correlation Coefficient. In addition, in-depth interview of 9 experts was also applied in order to obtain the qualitative data. The results shown that the significant administrative problem was the BMA’s insufficient operation on public relations or explanation of waste segregation to people by applying technology networking, as well as, lacking of administrative strategy for that matter whereas the appropriate guideline should explain to public and educate people in terms of waste segregation by applying through technology networking, such as, radio and television stations and various groups of community, including through social networking. Furthermore, the BMA should establish and implement administrative strategy of garbage collection services according to the sustainable administration concept consisting of 5 aspects, for example respectively: (1) establishment of knowledge and understanding widely, comprehensively, and throughout, (2) establishment of groups and mainstay of the community, (3) emphasis on development of organization and personnel master, (4) enhancement of understanding and consciousness, and (5) application of modern and appropriate technologies. Keywords: Administration, Garbage Collection, Services, The Bangkok Metropolitan Administration, the Sustainable Administration Concept